2007
DOI: 10.1159/000111760
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Histamine Improves Memory Retrieval of Inhibitory Avoidance by Lithium in Mice

Abstract: The influence of repeated administration of histamine on lithium-induced state dependency has been investigated. A single-trial step-down inhibitory avoidance task was used to assess memory in adult male NMRI mice. Intraperitoneal (i.p.) administration of lithium (10 mg/kg), immediately after training (post-training), impaired inhibitory avoidance memory on the test day. Pre-test administration of lithium reversed amnesia induced by the drug given after training, with the maximum response at a dose of 10 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…These results are in agreement with our prior study and other studies, which have found that systemic and/or intra-CA1 administration of lithium impairs memory formation by altering information coding and synaptic plasticity, resulting in induction of amnesia in a variety of tasks (Pachet and Wisniewski, 2003, Senturk et al, 2007, Zarrindast et al, 2008, Parsaei et al, 2016, Amiri et al, 2020. Hence, the effects of lithium on the brain may be particularly relevant to hippocampal-dependent cognitive processes.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with our prior study and other studies, which have found that systemic and/or intra-CA1 administration of lithium impairs memory formation by altering information coding and synaptic plasticity, resulting in induction of amnesia in a variety of tasks (Pachet and Wisniewski, 2003, Senturk et al, 2007, Zarrindast et al, 2008, Parsaei et al, 2016, Amiri et al, 2020. Hence, the effects of lithium on the brain may be particularly relevant to hippocampal-dependent cognitive processes.…”
Section: Discussionsupporting
confidence: 93%
“…For example, injection of the H 1 -antagonist pyrilamine into the amygdala was also found to impair memory functioning (Alvarez and Ruarte, 2004). Conversely, increasing histaminergic activity by pharmacologically blocking presynaptic H 3 -autoreceptors has been found to improve memory performance (Bacciottini et al, 2001;Zarrindast et al, 2008,). H 3 -antagonists have therefore attracted the attention of pharmaceutical companies as potential cognition enhancers.…”
Section: Introductionmentioning
confidence: 99%
“…It is accepted that synaptic plasticity is the cellular basis of emotional memory because long-term potentiation is correlated with memory trace formation (2). Studies have also investigated the effects of H 1 and H 2 histaminergic receptor activation on emotional memory in animals (9, 10) and humans (11). …”
Section: Introductionmentioning
confidence: 99%